TATA KELOLA KELOMPOK TANI SEBAGAI PENDUKUNG PENGEMBANGAN SEKTOR PERTANIAN - Purbayu Budi Santosa; Wiludjeng Roessali; Ariza Fuadi; Darwanto Darwanto (Universitas Muhammadiyah Semarang, 2017)
The agricultural sector is a sector that has a very strategic role in economic development in Indonesia. Nevertheless, the agricultural sector is still faced with several problems such as the unenforceability of farmers' welfare, lack of access to capital and marketing problems of crops. Kehadrian farmer groups and Sharia Micro Finance Institutions (LKMS) have not been able to optimize the potential of the agricultural sector. The purpose of this research is to analyze the institutional structure and network of local farmers and to analyze the institutional of local farmer groups. This research uses qualitative approach and collects data through indepth interview, focus group discussion (FGD) and obervation which involves participation of local agricultural sector actors by using qualitative analysis approach of case study with Analytical Network Process (ANP) analysis method. The results show that not all farmers in Central Java Province are incorporated in farmer groups and implement sharia financing system. Sharia financing system implemented by farmer groups through BMT and Savings and Loans Cooperative (KSP) has a positive impact on the development of farmers' farming in Central Java Keywords: inst itutional, farmer group, syariah financial inst itution, ANP.